Time-estimation of design process based on patterns - Szélig, Nikoletta; Vidovics, Balázs; Bercsey, Tibor (Periodica Polytechnica Mechanical Engineering, 2010)
The paper gives an overview on a new approach to estimate the time need of a design process. The product structure is identified by using a DSM, from which not only the components, but the design activities could be derived. To be able to use the experience data from previous design processes in the current situation, similarity matching and weighting is used. Exponential smoothing is used to calculate the time according to the weights. A network graph method, based on PERT serves as a basis of the graphical and mathematical representation.